INTERNAL CONTROL AS A MODERATING VARIABLE ON THE EFFECT OF DECENTRALIZATION ON MANAGERIAL PERFORMANCE - Nanik Hidayati; Wiwiek Dianawati (Universitas Airlangga, 2017)
In the context of implementing the Anggaran Pendapatan dan Belanja Negara (APBN), the Minister of Finance Regulation (PMK) No. 190/PMK.05/2012 concerning payment procedures in the context of implementing the APBN, which gives real authority and flexibility and is responsible for each work unit to manage state finances. To improve performance, one of the efforts made is to strengthen the internal control system. This study aims to determine whether the level of decentralization affects the managerial performance of BPS in East Java and to determine whether internal control strengthens the effect of the level of decentralization on the managerial performance of BPS in East Java. The research was conducted on the level of decentralization, internal control and managerial performance of Commitment Making Officers at the Central Statistics Agency in East Java. The results of the study stated that decentralization had no effect on managerial performance even though the direction was in line with what was predicted. In addition, internal control also does not strengthen the influence of decentralization on managerial performance even though the direction is in line with what was predicted.